Microwave assisted economic synthesis of 4-amino-3-alkyl-5-mercapto-1, 2, 4-triazole derivatives as green corrosion inhibitors for copper in hydrochloric acid - Dandia A.; Gupta S.L.; Sudheer; Quraishi M.A. (My University, 2025)
We have investigated a microwave-assisted cost effective synthesis of 3-substituted-4 amino-5-mercapto-1, 2, 4-trizole derivatives by condensation of different alkanoic acids and thiocarbohydrazide. We found that the use of microwave irradiation allows a rapid (4-8 min) and high-yielding (90-93%) reaction. The effect of synthesized triazoles on corrosion of copper in hydrochloric acid solution has been investigated by potentiodynamic polarization method. Potentiodynamic polarization measurements indicate that all three (AMT, AMMT and AEMT) examined compounds are cathodic type inhibitors. All the compounds exhibited more than 90% anticorrosion activity and highest is 96.09% by AEMT.